Pengaruh Pemberian Berbagai Dosis Curcuminoid pada Babi Terhadap Pertumbuhan dan Konversi Ransum - Silalahi M; Benedictus Benedictus; Sauland Sinaga (Jurnal Penelitian Pertanian Terapan, 2012)
Research about the effect of ration containing various dosage curcuminoid in pigs rations to growth rate and the ration conversion has been held since December 2005 until March 2006 in KPBI (Koperasi Peternak Babi Indonesia), Kecamatan Cisarua, Kabupaten Bandung. The purpose of this research is to know the Wright dosage of gives curcuminoid as feed additive also effect of curcuminoid as feed additive ration to growth rate and the ration conversion. This research was using 20 starter period pigs, age 2 months with weight rate 18 kg and variation coefficient 6.33%. The method was which used in this research is Complete Randomized Design with four level dosage of curcuminoid i.e, 0, 4, 8 and 12 mg/kg/body weight with five replications. The result of the research shows that giving curcuminoid as feed additive does not give the different effect to the ration conversion, but to growth rate by gives dosage of curcuminoid which 4 mg/kg/body weight effect to increase pigs growth rate. Curcuminoid which gives 4 mg/kg/body weight has give the best effect to growth rate and the ration conversion. KeyWords : Pigs, Feed Additive, Curcuminoid, Ration Conversion, Growth ate